The Smart Extensions Curriculum from an Islamic Educational Perspective - Ahmed Diaa El Din Hussein; Reem Abdul Razzaq Abdul Razzaq (Deanship of Scientific Research (DSR), the University of Jordan, 2023)
Objectives: This study aimed to reveal the foundations of the smart extensions curriculum and to clarify the concept behind it, its main elements, and the stages of building it, all from an Islamic educational perspective. Methods: Both inductive and deductive approaches were followed to study the smart extensions curriculum from an Islamic educational perspective. This involved first extrapolating the texts and referring to recent educational literature and studies to note the main features that indicate the nature of the curriculum. Additionally, educational deduction was directed towards inducted religious law texts and modern educational literature. The researchers also worked on tabulating the matrix of educational deductions in successive topics. Results: The foundations of the smart extensions approach are embodied in the legislative basis, which expresses the system of concepts and facts related to the beliefs and rulings brought by the Islamic religion. Furthermore, the psychological basis is expressed as a set of principles that take into account the conditions of individuals in terms of innate preparations, capabilities, needs, motives, desires and trends in light of authentic Islamic rules. The process of building the smart extensions curriculum has a number of stages, represented by the foundational framing stage, the formative organization stage, and the structural approval stage. Conclusions: This study recommends directing researchers to conduct scientific studies that are concerned with demonstrating the impact of revelation directives on building Islamic educational curriculums.